DAMPAK KOMPENSASI DAN BEBAN KERJA TERHADAP LOYALITAS KARYAWAN PADA PT. BERLIAN MULTI SEJAHTERA - Arifa Febriana; Kustini Kustini (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Human resources are an essential element in determining the smooth running of the organization's activities. Human resources as the company's most critical asset because their role has been used as the subject of company policies and operational activities. The level of employee loyalty in the company is strongly influenced by the compensation and workload given to employees. This study aims to determine the effect of compensation and workload on employee loyalty at PT. Berlian Multi Sejahtera. The sample size of this study was 55 people using the saturated sampling method—the collected data through questionnaires and interviews. The outer model test assessed the validity and reliability of the questionnaire first. In testing the hypothesis using the SEM PLS method, it is known that the t-test, p-values, and the original sample. The results that compensation contributes to employee loyalty, while workload does not contribute to employee loyalty.